Shared Space Creation from Intersubjective Temporality - , Aynaz Lotfata (Archives of Current Research International, 2019)
The study underlines that time is a socially practiced phenomenon and is a product of the interaction of socioeconomic and spatial practices in society. This study discusses an urban space where the process of globalization has intersected with the inter-subjective time to shape people daily life. The dialectical relationship between global and contextual temporalities defines the idea of planning and designing in the urban space. This study criticizes how local temporalities with those that are globally produced shape the shared space. The development of the embodied cognitions defines space, in which all members of a society find a way to culturally practice reality and experience time.